1968
DOI: 10.1084/jem.127.5.915
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Immunogenicity of Antigen After Uptake by Macrophages

Abstract: Macrophages have the important function of participating with other cells like polymorphonuclear leukocytes (PMNs) in the uptake of bacteria, virus, and miscellaneous foreign proteins. After the uptake of these materials, both macrophages (1, 2) and PMNs (3) can catabolize them in a rapid and efficient way. (There are important exceptions however; macrophages do not catabolize well Mycobacterium tuberculosis [4], pneumococcal polysaccharide [5], or synthetic polymers of D-amino acids [6] ). In addition, live m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(56 citation statements)
references
References 20 publications
6
50
0
Order By: Relevance
“…These cells may degrade most of the antigen which they ingest, but in some cases they retain a small fraction of it for some time, and this is suitable for induction of antibodies (24)(25)(26). In fact, this retained fraction may be particularly evocative of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…These cells may degrade most of the antigen which they ingest, but in some cases they retain a small fraction of it for some time, and this is suitable for induction of antibodies (24)(25)(26). In fact, this retained fraction may be particularly evocative of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Using Maia squinado hemocyanin (MSH) as antigen, Unanue and Askonas (1968a) found that antigen associated with macrophages was more effective in priming animals for a subsequent secondary response than was free antigen. Macrophage-associated M SH produced a secondary re sponse in irradiated recipients provided that normal lymphoid cells were also administered.…”
Section: Several Lines Of Investigation Have Shown That Macrophages Maymentioning
confidence: 99%
“…I t is apparent from the above reports that studies of the radiationsensitivity of macrophages are conflicting (Mitchison, 1969a;Unanue and Askonas, 1968a;Roseman, 1969;Pribnow and Silverman, 1967).…”
Section: Several Lines Of Investigation Have Shown That Macrophages Maymentioning
confidence: 99%
“…The discovery by Miller (12) and by Good (13) that lymphocytes differentiate into two separate classes of cells (T and B) with distinct functions, the identification of cellular immune phenomena mediated by T cells (14) and the demonstration that immune responses are regulated by helper (15,16,17) and suppressor (18,19) cells and by macrophages (20) emphasized the complexity of the immune system and the critical role played by T lymphocytes in the regulation of immunity.…”
mentioning
confidence: 99%